Molecular docking, anti-proliferative activity and induction of apoptosis in human liver cancer cells treated with androstane derivatives: Implication of PI3K/AKT/mTOR pathway. Issue 198 (April 2020) - Kattan, Shahad W.; Nafie, Mohamed S.; Elmgeed, Gamal A.; Alelwani, Walla; Badar, Muhammad; Tantawy, Mohamed A.
Graphical abstract: Highlights: Six androstane derivatives were evaluated against hepatocellular carcinoma cell line (HepG2). Compound 4 and 5 showed very promising activity against HepG2 cells, with un-toxic effect against normal cells. Compound 4 could inhibit PI3K/AKT/mTOR pathway, associated with cell cycle arrest, activation of both extrinsic and intrinsic apoptosis pathway. Compound 4 could be promising chemical scaffold for the development of future leads as anti-HCC agents. Abstract: Worldwide, cancer is still an area with high unmet medical need. Lead optimization efforts towards structure-based drug design were employed to discover newly synthesized hetero-steroid derivatives with promising anticancer effects against hepatocellular carcinoma (HCC). The aim of our study is to evaluate the anti-proliferative activity and the mechanism, a dual PI3K/mTOR inhibitor, and mechanism of action of a series of heterocylic androstane derivatives as anti-HCC agent. The cytotoxic effects of different heterocylic androstanes and 5FU as single agents, were assessed against both HepG2 cells and Non-malignant MDCK cell line to assess the toxicity. Then the underlying mechanism of compound 4 as most promising compound was evaluated using molecular docking, MTT assay, cell cycle analysis, DNA fragmentation, and real-time PCR. The results of MTT assay showed potential cytotoxic effect for compound 4 and 5 against liver cancer cell line with IC50 value 39.81 and 57.54 μM, respectively. Inhibition of the PI3K/AKT/mTOR pathway was achieved by compound 4, which was documented by molecular docking and augmented by gene expression analysis. Detailed mechanism revealed that compound 4 induced cell cycle arrest, DNA fragmentation, and induction of apoptosis by inhibition of anti-apoptotic genes, and upregulation of apoptotic genes. Our results shed a light on aminopyrazoloandrostane derivative 4 as an inhibitor of the PI3K/AKT/mTOR pathway, which might be acting as promising anti-liver cancer agent. Our data support further investigation of agents targeting the PI3K/AKT/mTOR.